Molecular characterization of chicken DA systems reveals that the avian personality gene, DRD4, is expressed in the mitral cells of the olfactory bulb - Fujita, Toshiyuki; Aoki, Naoya; Mori, Chihiro; Homma, Koichi J.; Yamaguchi, Shinji (Frontiers in Neuroanatomy, 2025)
Animal personalities are stable, context-dependent behavioral differences. Associations between the personality of birds and polymorphisms in the dopamine receptor D4 (DRD4) gene have been repeatedly observed. In mammals, our understanding of the role of the dopamine (DA) system in higher cognitive functions and psychiatric disorders is improving, and we are beginning to understand the relationship between the neural circuits modulating the DA system and personality traits. However, to understand the phylogenetic continuity of the neural basis of personality, it is necessary to clarify the neural circuits that process personality in other animals and compare them with those in mammals. In birds, the DA system is anatomically and molecularly similar to that in mammals; however, the function of DRD4 remains largely unknown. In this study, we used chicks as model birds to reveal the expression regions of the DA neuron-related markers tyrosine hydroxylase (TH), dopa decarboxylase (DDC), dopamine β-hydroxylase (DBH), and DRD4, as well as other DRDs throughout the forebrain. We found that DRD4 was selectively expressed in the mitral cells of the olfactory bulb (OB). Furthermore, a detailed comparison of the expression regions of DA neurons and DRD4 in the OB revealed a cellular composition similar to that of mammals. Our findings suggest that the animal personality gene DRD4 is important for olfactory information processing in birds, providing a new basis for comparing candidate neural circuits for personality traits between birds and mammals.